2016
DOI: 10.1016/s2095-3119(16)61409-0
|View full text |Cite
|
Sign up to set email alerts
|

The causes and impacts for heat stress in spring maize during grain filling in the North China Plain — A review

Abstract: High-temperature stress (HTS) at the grain-filling stage in spring maize (Zea mays L.) is the main obstacle to increasing productivity in the North China Plain (NCP). To solve this problem, the physiological mechanisms of HTS, and its causes and impacts, must be understood. The HTS threshold of the duration and rate in grain filling, photosynthetic characteristics (e.g., the thermal stability of thylakoid membrane, chlorophyll and electron transfer, photosynthetic carbon assimilation), water status (e.g., leaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 80 publications
1
18
1
1
Order By: Relevance
“…Therefore, to fully exploit the yield potential of maize sole cropping systems, we should provide a suitable climate condition for maize growth, namely, an optimal sowing date. Numerous previous studies have studied the optimization of the sowing date and investigated the effect of different sowing dates on spring or summer maize in NCP [5,[21][22][23][24][25]. On the one hand, the optimal sowing date can provide maize with relatively appropriate climate conditions, such as sufficient natural light, temperature, and precipitation resources.…”
Section: In 1900mentioning
confidence: 99%
“…Therefore, to fully exploit the yield potential of maize sole cropping systems, we should provide a suitable climate condition for maize growth, namely, an optimal sowing date. Numerous previous studies have studied the optimization of the sowing date and investigated the effect of different sowing dates on spring or summer maize in NCP [5,[21][22][23][24][25]. On the one hand, the optimal sowing date can provide maize with relatively appropriate climate conditions, such as sufficient natural light, temperature, and precipitation resources.…”
Section: In 1900mentioning
confidence: 99%
“…The increasing average temperature at present could accelerate the maize growth rate and shorten the growing season (Xiao et al ., 2016; Wang et al ., 2018c; Lv et al ., 2020; Xiao et al ., 2019). Furthermore, high temperature stress (temperature over the daily maximum temperature threshold of 35°C at stage 1–3 and 33°C at stage 4) can limit photosynthesis, negatively affect plant water status, increase abscisic acid, further affect pollen viability and fertilization, reduce the grain‐filling rate, shorten the grain‐filling stage, and reduce kernel weight (Tao et al ., 2013; Mayer et al ., 2014; Hatfield and Prueger, 2015; Tao et al ., 2016; Siddik et al ., 2019). It has been confirmed that temperature will increase with a likelihood in the future under both RCP4.5 and RCP8.5, which not only shorten the growth and grain filling period but also greatly affect pollen viability and fertilization.…”
Section: Discussionmentioning
confidence: 99%
“…Сучасні дослідження спрямовані на визначення агрономічної продуктивності, стійкості та механізмів адаптації рослин до компонентів клімату та екологічних стресів (Wijewardana et al, 2016), зокрема, екстремальних холодових і теплових впливів (Tao et al, 2016), дефіциту води та підвищеної солоності (Álvarez and Sánchez-Blanco, 2015;Zheng et al, 2015;Bendaly et al, 2016). Автори відмічають наявність зв'язку між фізіологічними показниками, екологічними факторами та процесами фотосинтезу в рослинах.…”
Section: вступunclassified